IMPLEMENTATION OF RELIGIOUS MODERATION EDUCATION THROUGH EXTRACURRICULAR ACTIVITIES AT VOCATIONAL HIGH SCHOOL - Sukarman; Subaidi; Ainul Ghuri; Azzah Nor Laila; Abdulazizkalupae (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This article explores the implementation of religious moderation education through extracurricular activities in vocational high schools. This research uses a qualitative approach that is analytically descriptive. The research location is at SMK 17 August Bangsri Jepara. Data collection in this study used interview techniques, observation, documentation studies, literature studies, and field notes. The data analysis is like Miles and Huberman, namely: data reduction, data presentation, and conclusion drawing. In this study obtained the results that religious moderation education at SMK 17 August Bangsri Jepara can be carried out through several strategies, among others: First, extracurricular activities of scouts. To produce moderate scout members, of course, they must be accompanied by moderate mentors to teach the value of religious moderation; Second, camp activities: Ambalam Guest Reception Camp. In this activity, scouts are taught to respect various religious beliefs, teach moral values, and develop positive religious attitudes. One of the activities taught is the appreciation of the Dasa Darma Scout is very important and can be applied to extracurricular scouting activities to shape the character of participants for the better, in this case the attitude of religious moderation; Third, camp activities: Bantara Camp. In this case, participants are taught some education, including: character building, life skills, and social care. One of them is the Scout Oath, this activity has a positive impact in encouraging moderate attitudes for participants and also for participants at school. Manifestations of moderate education for participants include: universal values; openness; tolerance; and cooperation.